KAJIAN REHABILITASI MANGROVE DI PULAU BATANTA KOTA SORONG BERBASIS EKOSISTEM TERPADU - Alfred A Antoh (NOVAE GUINEA Jurnal Biologi, 2015)
AbstractConsidering the condition of Batanta Island and the potencies of its natural resources, it is necessary to study the characteristics of its natural resources, appropriate utilization, and conservation efforts, including the rehabilitation of mangroves.Â  The result of the research shows that such plants as Perepat (Sonneratiaalba), Api-api (Avicenniaofficinalis) and Bakau (Rhizophoraapiculata) can be planted in the planned site. Perepat and Api-api are thought to be species that have excellent survivability (able to grow into mature plants), and the construction design for the rehabilitation should use alluvial soil as the media and be filled as high as 190 meters. A massive concrete embankment is constructed in the northern part and stone embankment in the western part of the mangrove rehabilitation site, an area of 11.7 square hectares.Keywords: management, ecosystem, coastal resources, Small Island